Partial differential equations II: Qualitative Studies of Linear Equations - Taylor, Michael E. (New York : Springer, 2011)
This text provides an introduction to the theory of partial differential equations. It introduces basic examples of partial differential equations, arising in continuum mechanics, electromagnetism, complex analysis and other areas, and develops a number of tools for their solution, including particularly Fourier analysis, distribution theory, and Sobolev spaces. These tools are applied to the treatment of basic problems in linear PDE, including the Laplace equation, heat equation, and wave equation, as well as more general elliptic, parabolic, and hyperbolic equations. Companion texts, which take the theory of partial differential equations further, are AMS volume 116, treating more advanced topics in linear PDE, and AMS volume 117, treating problems in nonlinear PDE. --
1. Basic theory -- 2. Qualitative studies of linear equations -- 3. Nonlinear equations.
"There are seven additional chapters in this edition, two in Volume I, two in Volume II, and three in Volume III. In addition, several other sections have been substantially rewritten, and numerous others polished to reflect insights gained through the use of these books over time"--P. xxii.
Includes bibliographical references and index.
LC has: vols. 1-2, only.
Keywords: Differential equations, Partial